A longitudinal study of the diabetic skin and wound microbiome - Gardiner,Melissa; Vicaretti,Mauro; Sparks,Jill; Bansal,Sunaina; Bush,Stephen; Liu,Michael; Darling,Aaron; Harry,Elizabeth; Burke,Catherine M. (PeerJ, 2017)
Background Type II diabetes is a chronic health condition which is associated with skin conditions including chronic foot ulcers and an increased incidence of skin infections. The skin microbiome is thought to play important roles in skin defence and immune functioning. Diabetes affects the skin environment, and this may perturb skin microbiome with possible implications for skin infections and wound healing. This study examines the skin and wound microbiome in type II diabetes. Methods Eight type II diabetic subjects with chronic foot ulcers were followed over a time course of 10 weeks, sampling from both foot skin (swabs) and wounds (swabs and debrided tissue) every two weeks. A control group of eight control subjects was also followed over 10 weeks, and skin swabs collected from the foot skin every two weeks. Samples were processed for DNA and subject to 16S rRNA gene PCR and sequencing of the V4 region. Results The diabetic skin microbiome was significantly less diverse than control skin. Community composition was also significantly different between diabetic and control skin, however the most abundant taxa were similar between groups, with differences driven by very low abundant members of the skin communities. Chronic wounds tended to be dominated by the most abundant skin Staphylococcus, while other abundant wound taxa differed by patient. No significant correlations were found between wound duration or healing status and the abundance of any particular taxa. Discussion The major difference observed in this study of the skin microbiome associated with diabetes was a significant reduction in diversity. The long-term effects of reduced diversity are not yet well understood, but are often associated with disease conditions.
Keywords: Diabetes; Diabetic ulcer; Diversity; Skin microbiome; 16S rRNA gene sequencing